Impact of corporate social responsibility intensity on corporate reputation and financial performance of Indian firms - Pradhan, Sudeepta (Business: Theory and Practice, 2016)
The rising importance of CSR over the last few decades has stirred the interest of academia and corporate on the subject. CSR attracted attention in the Indian context with the implementation of the Companies Bill, 2013, which mandated firms to invest 2 per cent of their net profits in social activities. The linkages between CSR and profitability using factors such as corporate reputation, competition intensity, and advertising have been tested in the developed countries. These linkages have sparsely been tested in emerging economies such as India, which motivated me to conduct this study. Neville et al. (2005) proposed a theoretical model integrating stakeholders, and internal and external factors influencing the CSR-FP relationship. This study modified and used Neville’s et al. (2005) model to test the proposed linkage in the Indian context. Structural Equation Modeling revealed a significant relationship between CSR Intensity and corporate reputation; significant role of social initiative and corporate strategy fit in enhancing the corporate reputation of a firm; and a significant role of advertising and promotion in enhancing corporate reputation. Other variables such as competitive intensity, supplier power, customer power and employee power were found to have no significant role on the proposed relationships.